Technical Efficiency Analysis of Potato Farming in Kerinci Regency-Indonesia (Approach Data Envelopment Analysis Method) - Fitri, Yanuar; Nainggolan, Saidin (International Journal of Environment, Agriculture and Biotechnology, 2022)
Kerinci regency is the highest production area compared to other potato centers. Kerinci regency has the most composition of 92.98 percent or as much as 76477.4 tons with, productivity of 17.06 tons / ha. The scope of this research is focused on knowing the use of production factors and the level of technical efficiency of respondent farmers. The research was conducted within the scope of West Kayu Aro District, Kerinci District, Jambi Province. The analysis tool used is Data Envelopment Analysis, with input-oriented Return To Scale (VRS) Variable models. The use of inputs in seed potato farming activities as much as 2315,403 kg / ha, SP 36 fertilizer as much as 191,129 kg / ha, KCl fertilizer as much as 137,258 kg / ha, phonska fertilizer 157,419 kg / ha fungicide as much as 452.9 gr / ha, insecticides of 597.4 gr / ha, and labor 73.2 HOK / ha / MT. The average value of technical efficiency obtained by farmers respondents to the research area was 0.936 with the highest value of 1 and the lowest value of 0.763. Farmers respondents who are classified on the IRS scale as many as 21 people or by 33.9 percent, DRS as many as 10 people by or 16.1 percent, and CRS as many as 31 people or by 50 percent.